Development of Smart Box Learning Media to Increase Student Learning Interest in the Material of Cultural Diversity of the 7th Grade Community SMP Bahrul Maghfiroh - Istiqomah, Nailatul; Listyo Yudha Irawan (Institut Agama Islam Negeri Ponorogo, 2025)
Low student interest in learning is one of the inhibiting factors in achieving optimal learning outcomes, especially in the material on the diversity of community culture. This condition encourages the need for innovation in delivering material through interesting and interactive learning media. This study aims to develop Smartbox learning media as a means to increase the learning interest of 7th grade students of Bahrul Maghfiroh Middle School. The method used is research and development (Research and Development) with the ADDIE model which is modified into several core stages, including: analysis, design, development, implementation, and evaluation. The results of the study showed that the Smartbox media developed received a